2017
DOI: 10.3389/fphar.2017.00571
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide, a New Hope in the Prevention and Treatment of Metabolic Syndrome

Abstract: Recently, the use of plant-derived medicines is increasing interest in the prevention and treatment of a variety of disorders including metabolic syndromes. Metabolic syndrome is one of the major risk factors for cardiovascular diseases (CVDs) and incidence of mortality worldwide. Scientific evidence suggests that Andrographis paniculata and its derived components, especially andrographolide (AGL) and its analogs/derivatives have a broad spectrum of biological activities. This review aims to sketch the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 53 publications
(75 reference statements)
0
34
1
Order By: Relevance
“…A. paniculata and andrographolide exhibit an extremely wide array of pharmacological activities 4,425,488–492 including adaptogenic, 160 antioxidant, chemopreventive, 4 and neuroprotective activities 361,493–496 …”
Section: Core Rational Of the Adaptogenic Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…A. paniculata and andrographolide exhibit an extremely wide array of pharmacological activities 4,425,488–492 including adaptogenic, 160 antioxidant, chemopreventive, 4 and neuroprotective activities 361,493–496 …”
Section: Core Rational Of the Adaptogenic Conceptmentioning
confidence: 99%
“…486 In another study, the aqueous extract of A. paniculata was shown to attenuate gentamicin-induced nephrotoxicity decreasing blood levels of urea, creatinine, and urea nitrogen levels in rats. 487 A. paniculata and andrographolide exhibit an extremely wide array of pharmacological activities 4,425,[488][489][490][491][492] including adaptogenic, 160 antioxidant, chemopreventive, 4 and neuroprotective activities. 361,[493][494][495][496] The cytoprotective effect of several adaptogenic plant extracts on chemotherapeutics-induced dramatic impact on transcriptome-wide RNA microarray profiles of neuroglia cells culture have been recently studied.…”
Section: Molecular Mechanisms Of Action-effects On Intracellular Simentioning
confidence: 99%
“…In recent years, active compounds from natural products have gained attention for potential use in interventions against cancer progression and metastasis. Andrographolide, a diterpenoid lactone derived from Andrographis paniculata Nees, a herbal medicine widely used across Southeast Asian countries (Sareer et al, 2014) has been shown to exhibit a broad range of pharmacological properties (Gupta et al, 2017; Islam, 2017; Yang et al, 2017), and many recent studies have revealed its promising anticancer effects (Lim et al, 2012; Mishra et al, 2015). It has been shown to suppress cancer cell proliferation by disrupting proteins related to cell cycle regulation and to inhibit MCF-7 breast cancer cell proliferation by inducing G1 cell cycle arrest through increased p27 and decreased CDK4 (Rajagopal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The derivative of Andro decreased histopathological changes, the recruitment of immune-inflammatory cells, and the secretion of pro-inflammatory cytokines to produce anti-inflammatory effects ( Liu et al, 2014 ; Yang et al, 2016 ). It was reported that Andro improved diabetes and ameliorated diabetic-related complications through reducing the expression of pro-inflammatory cytokines ( Islam, 2017 ). Andro suppressed LPS-induced microglial MIP-1α, P2X7 receptor, and its downstream signaling mediators including inflammasome NLRP3, caspase1, and mature IL-1β ( Das et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%